Sight-specific development of the tools for the measurement of CO2-emission of the soil - Kovács, Györgyi; Szőllősi, Nikolett (Acta Agraria Debreceniensis, 2008)
Soil is the main source and at the same time the potential sink of greenhouse gases (e.g. CO2, CH4). Measurements were carried out in the experimental sites (soil tillage experiments and an extensive pasture) of the Karcag Research Institute of University of Debrecen, Centre for Agricultural Sciences to determine the CO2-emission of the soil. The in situ CO2-emission of soil was measured by means of an ANAGAS 98 infrared gas analyser in plastic (PVC) chambers, but this previously applied method (cylinders) was not suitable for the soil surface covered with grass,hence a new instrument was needed to be invented. In order to measure CO2-emission on a larger area without deep disturbance of the soil, a special metal frame was created with a matching bowl. The most problematic part was the spatial delimitation of the measurement area as the surface of the soil can be very various and proper isolation is a must. We consider the frame+bowl method we developed suitable for measuring CO2-emission of pastures as well as other crop-fields.